The relationship between headmasters' leadership style and empowerment / Royneal Rosidih - Rosidih, Royneal (2014)
The purpose of this study was to identify the relationship between Headmasters' leadership style and empowerment. Six primary schools from four types of school namely Daily- Primary school, Residential Primary School, 'Sekolah Kurang Murid' SKM (under enrolment school) and Mission School. Data were collected using questionnaire and interview techniques. The questionnaire was distributed to all the teachers in all six selected schools using cluster sampling. A number of 120 questionnaires were distributed to teacher respondents and a number of 104 questionnaires were collected, which were complete and usable for the analysis. Data were analyzed using descriptive and inferential statistics. The findings showed that Transformational leadership style was the most practiced leadership style followed by Transactional leadership style and lastly Laissez-faire leadership style. Other than that, the findings also revealed that level of empowerment in all dimensions was moderate. In addition, findings indicated that there was a significant relationship between Transformational leadership style and Transactional leadership style with decision making, professional growth, status, self-efficacy and impact. However there was no significant relationship between Transformational leadership style and Transactional leadership style with autonomy. Other than that, Laissez-faire leadership style does not show any significant relationship with any of the empowerment dimensions. The study also showed no significance difference in all the demographic factors namely gender, age group, highest academic qualification or experience in teaching. The findings have implications for the role of teachers to enhance empowerment of all dimensions in school. Based on the findings, this study also provides several recommendations for the improvement of practice and future research in the area of study.